Penerapan Metode Menghafal Al-Qur'an oleh Guru PAI di SD Negeri 19 Air Tawar Barat - Deswita, Meisya Rahma; Murniyetti, Murniyetti (Asian Journal of Islamic Studies and Da'wah, 2023)
The purpose of this research is to find out how the application of the Al-Quran memorization method by PAI Teachers and to find out the supporting and inhibiting factors in applying the Al-Quran memorization method at SD Negeri 19 Air Tawar Barat. This research uses a qualitative method with a descriptive approach. This research was conducted at SD Negeri 19 Air Tawar Barat in Padang city. The data collection techniques used were observation, interview and documentation. The informants in this study were the Principal, PAI Teacher and students. The results showed that, (1) The application of the Quran memorization method at SD Negeri 19 Air Tawar Barat has several stages, namely planning implementation and evaluation. (2) Supporting factors for the application of the Tallaqi and Jama'i methods are the motivation of the teacher, good cooperation between PAI teachers and class teachers, parents and using juz 'amma. The inhibiting factors are laziness and impatience, the different abilities of students and the lack of supporting facilities and infrastructure.